2022
DOI: 10.3390/brainsci12030363
|View full text |Cite
|
Sign up to set email alerts
|

Neurofeedback-Augmented Mindfulness Training Elicits Distinct Responses in the Subregions of the Insular Cortex in Healthy Adolescents

Abstract: Mindfulness training (MT) reduces self-referential processing and promotes interoception, the perception of sensations from inside the body, by increasing one’s awareness of and regulating responses to them. The posterior cingulate cortex (PCC) and the insular cortex (INS) are considered hubs for self-referential processing and interoception, respectively. Although MT has been consistently found to decrease PCC, little is known about how MT relates to INS activity. Understanding links between mindfulness and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 135 publications
1
5
0
4
Order By: Relevance
“…Compared with the control group, in which no statistically significant change was observed, the neurofeedback-assisted meditation group showed a remarkable decrease in the PSS score, which was meaningful as it confirmed the effect of neurofeedback-assisted meditation treatment over time. 39 This is consistent with the results of previous studies showing that practicing mindfulness meditation had a positive effect on stress reduction. This implies that the effect of neurofeedback assistance can further maximize the effect of meditation over a short period of time.…”
Section: Discussionsupporting
confidence: 92%
“…Compared with the control group, in which no statistically significant change was observed, the neurofeedback-assisted meditation group showed a remarkable decrease in the PSS score, which was meaningful as it confirmed the effect of neurofeedback-assisted meditation treatment over time. 39 This is consistent with the results of previous studies showing that practicing mindfulness meditation had a positive effect on stress reduction. This implies that the effect of neurofeedback assistance can further maximize the effect of meditation over a short period of time.…”
Section: Discussionsupporting
confidence: 92%
“…The final paper in the Special Issue [ 41 ] examined the neural effects of mindfulness training: in particular, how the insula—a key interoceptive brain area—might be modulated in healthy adolescents. Given that some studies have shown changes to interoception following mindfulness training, it is to be expected that changes to interoceptive brain regions also occur.…”
Section: Non-clinical Researchmentioning
confidence: 99%
“…Mindfulness training (MT) shows promise as an early intervention to help prevent mental health issues and increase wellbeing in adolescents [ 45 ], and it is possible it may exert its effects via changes to interoception. Yu and colleagues [ 41 ] sought to test whether MT causes changes in interoceptive brain regions in adolescents. They employed fMRI-based neurofeedback-augmented mindfulness training, and found the differential effects of neurofeedback runs on sub-regions of the insula: increases in the activation of the anterior insula and decreases in the posterior insula.…”
Section: Non-clinical Researchmentioning
confidence: 99%
“…Taken together, these findings highlight the PCC’s clinical relevance in PTSD psychopathology and suggest that regulating activity within the region via rt-fMRI-NFB may generate positive clinical outcomes. Critically, however, very few studies have examined the neurobiological mechanisms associated with the regulation of the PCC with rt-fMRI-NFB ( Zhang et al, 2013 ; Garrison et al, 2013a , b ; Kirlic et al, 2022 ; Yu et al, 2022 ), with only one study examining the regulation of this region in PTSD ( Nicholson et al, 2021 ; Lieberman et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%